Integrating Tradition and Modernity: Infrastructure Transformation at Al-Ustmani Islamic Boarding School in East Java - Zaini, Mohammad; Munib, Bahrul; Hatta, Hatta (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study explores the evolution of infrastructure and facilities at Al-Ustmani Islamic Boarding School in Bondowoso, East Java, focusing on how the institution balances traditional Salafiyah values with modern educational demands. Researchers used a qualitative descriptive method to gather data through semi-structured interviews, on-site observations, and document reviews. Perspectives from caregivers, teachers, administrators, and students were analyzed to reveal how infrastructure advancements relate to educational quality. The findings show a significant transition from basic facilities to modern, well-equipped structures, guided by a strategic approach to enhance learning environments while preserving the pesantren’s traditional identity. Improvements such as modernized classrooms, dormitories, libraries, and vocational training centers have led to greater student engagement and academic achievement. This harmonious integration of Islamic traditions with formal education has solidified the school’s role in fostering religious, intellectual, and socio-economic progress. Innovative initiatives like independent business units and vocational training programs demonstrate the pesantren’s commitment to preparing students for contemporary challenges. Information technology and entrepreneurship training underscores the school’s dedication to comprehensive student development. These advancements highlight the institution’s ability to adopt globalization and technological innovations without sacrificing its cultural and educational principles. This research contributes to discussions on the evolution of Islamic education by offering a replicable framework for merging traditional values with modernity in pesantren. It emphasizes the importance of holistic management to maintain relevance and excellence in an ever-changing educational landscape.